Knowledge, attitudes, and practices among patients with diabetes mellitus and hyperuricemia toward disease self-management - Wang, Dan; Liu, Zhixin; Liu, Yu; Zhao, Lingfei; Xu, Lijuan; He, Shanshan; Duan, Binhong (Frontiers in Public Health, 2024)
Background: This study aimed to assess the knowledge, attitudes and practices (KAP) among patients with diabetes mellitus and hyperuricemia towards disease self-management. Methods: This web-based cross-sectional study was conducted between June 2023 and January 2024 at Heilongjiang Provincial Hospital. A self-designed questionnaire was developed to collect demographic information of patients with diabetes mellitus and hyperuricemia, and assess their knowledge, attitudes and practices toward disease self-management. Results: A total of 482 participants were enrolled in this study, among them, 364 (75.52%) were male, 235 (48.76%) were aged between 40 and 59 years, 226 (46.89%) had a body mass index (BMI) ranging from 24 to 28 kg/m2, 337 (69.92%) had received a diagnosis of diabetes for a duration of 2 years or more, while 245 (50.83%) had been diagnosed with hyperuricemia for a similar duration. Their median (range) knowledge, attitude and practice scores were 10.00 (9.00, 11.00) (possible range: 0-12), 38.00 (36.00, 40.00) (possible range: 9-45), and 30.00 (26.00, 34.75) (possible range: 10-50), respectively. The path analysis demonstrated that knowledge had direct effects on attitude (β = 0.508, P < 0.001), and attitude had direct effects on practice (β = 0.448, P < 0.001). Additionally, there was an indirect effect of knowledge on practice mediated through attitude, with a path coefficient of 0.228 (P < 0.001). Conclusion: This study demonstrates that patients with diabetes mellitus and hyperuricemia exhibit relatively proficient responses to certain items within the KAP dimensions. However, it also exposes a certain degree of inadequacy in the KAP level toward disease management. Interventions should focus on improving patients' understanding of their conditions while fostering positive attitudes, ultimately translating into better self-management practices.